Proceedings of the 2014 ACM/IEEE International Conference on Human-Robot Interaction 2014
DOI: 10.1145/2559636.2559657
|View full text |Cite
|
Sign up to set email alerts
|

Robot deictics

Abstract: As robots collaborate with humans in increasingly diverse environments, they will need to effectively refer to objects of joint interest and adapt their references to various physical, environmental, and task conditions. Humans use a broad range of deictic gestures-gestures that direct attention to collocated objects, persons, or spaces-that include pointing, touching, and exhibiting to help their listeners understand their references. These gestures offer varying levels of support under different conditions, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…Previous work in human robot-interaction on how coverbal gestures affect comprehension has largely focused on pointing (deictic) gestures [5][23] [28], revealing that better understanding of relative locations of referents was achieved by supplementing speech information with deictic gestures. This provides some first evidence for speech and gesture integration.…”
Section: Gestures In Human-robot Interactionmentioning
confidence: 99%
“…Previous work in human robot-interaction on how coverbal gestures affect comprehension has largely focused on pointing (deictic) gestures [5][23] [28], revealing that better understanding of relative locations of referents was achieved by supplementing speech information with deictic gestures. This provides some first evidence for speech and gesture integration.…”
Section: Gestures In Human-robot Interactionmentioning
confidence: 99%
“…When presented with speech, robot-performed pointing (deictic) gestures [8][9] [10], revealed that better understanding of relative locations of referents could be achieved by supplementing speech information with such gestures. Thus providing evidence for speech and gesture integration.…”
Section: B Gestures In Human-robot Interactionmentioning
confidence: 99%
“…First studies using coverbal pointing gestures to improve robot communication seem to suggest that, at least for pointing, such integration can occur [8][9] [10]. Other types of gestures, however, have not yet been examined.…”
Section: Introductionmentioning
confidence: 99%
“…Robots will require an understanding of how gesture choice can affect communication in order to communicate with their human partners. To better inform our understanding of deictic gestures, I designed and implemented six different deictic gestures from literature and evaluated them in six diverse scenarios that represent physical, environmental, and task conditions under which robots are expected to employ deictic referencing [5]. For each gesture, participants identified the accuracy with which the gesture communicated and rated the effectiveness and naturalness of the robots gestures.…”
Section: Study 3: Deictic Gestures (Completed)mentioning
confidence: 99%